2002
DOI: 10.1089/107632702320934100
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Chitosan as a Cell Scaffold Material for Cartilage Tissue Engineering

Abstract: One of the most important factors in any tissue-engineering application is the cell substrate. The purpose of this study was the initial evaluation of chitosan, a derivative of the abundant, naturally occurring biopolymer chitin, as a cell scaffold for cartilage tissue engineering. Chitosan scaffolds having an interconnecting porous structure were easily fabricated by simple freezing and lyophilization of a chitosan solution. After rehydration of scaffolds, porcine chondrocytes were seeded onto scaffolds and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(202 citation statements)
references
References 37 publications
5
191
0
6
Order By: Relevance
“…Rapid degradation [170] [171]; [172]; [173]; [174] Alginate Aids re-differentiation of de-differentiated chondrocytes [66] In vivo injectable options [175] Abundant and low cost Certain cross-linkage can result in poor biocompatibility [184]; [185]; [186]; [187]; [188]; [189]; [182]; [190] Dermatan sulphate, [194]; [195] …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Rapid degradation [170] [171]; [172]; [173]; [174] Alginate Aids re-differentiation of de-differentiated chondrocytes [66] In vivo injectable options [175] Abundant and low cost Certain cross-linkage can result in poor biocompatibility [184]; [185]; [186]; [187]; [188]; [189]; [182]; [190] Dermatan sulphate, [194]; [195] …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…It should be noted that the defect in the blank group was partially repaired (Figs. 3d-3f, 5d-5f, and 6d-6f), which indicates that, because of its biocompatibility and antibacterial properties, pure chitosan hydrogel can also promote cartilage damage repair (Nettles et al, 2002). During the process of repair, the gel will be gradually replaced by cartilage tissue.…”
Section: Discussionmentioning
confidence: 97%
“…Alginate-chitosan microcapsules have been used to encapsulate mouse osteoblastic MC3T3-E1 cells (Qiao et al, 2014), and the results showed that the activity of cells in the alginate-chitosan microcapsules exceeded that of the alginate microcapsule group, which proved that chitosan has excellent biocompatibility. Nettles et al (2002) demonstrated that cartilage cells can adhere for a long time to chitosan scaffolds, which keeps their morphological characteristics. These studies indicated that chitosan is a desirable scaffold for the repair of cartilage defects.…”
Section: Introductionmentioning
confidence: 98%
“…Chitosan-based scaffolds have been extensively studied for bone and cartilage tissue engineering applications. [15] The application of chitosan in cartilage tissue engineering is due to its ability to electrostatically attract GAGs. [16] Apart from this, chitosan-based polymeric constructs were found to sufficiently adhere to the cartilage surface and have been used for the rectification of the chondral articular defects.…”
Section: Scaffold Fabrication Techniquementioning
confidence: 99%